Renkou jiaoyu gua tu
'Population education hanging charts.' Series of 18 sheets. (Sheet 6 missing, sheet 7 in duplicate), "head" and "tail", explanatory booklet, in one plastic bag. Population education hanging charts. Late 1980's. Printno. 7012.0629.